Annual occurrence of Red Knot Calidris canutus rufa at Punta Rasa, Samborombón Bay, Argentina, over a 30-year period (1985–2014) - Martínez Curci, Natalia Soledad; Bremer, Esteban; Azpiroz, Adrián B.; Battaglia, Gabriel E.; Salerno, Javier C.; Isacch, Juan Pablo; González, Patricia M.; Castresana, Gabriel J.; Rojas, Pablo (Wader Study)
From 1985 to 2014, we monitored numbers of Red Knots Calidris canutus of the subspecies rufa occurring at Punta Rasa, Samborombón Bay, Buenos Aires province, Argentina during northward migration (March to April), and in the austral winter (mid-May to mid-August), when some knots, mainly immatures, remain in South America during the breeding season. Numbers occurring during northward migration declined over the monitoring period from a peak of 3,640 in 1987 to 168 in 2014. This is consistent with the concurrent decline of the main Tierra del Fuego wintering population (though the percentage of the Tierra del Fuego population stopping at Punta Rasa also declined from 5.4% to 1.3%). Numbers occurring at Punta Rasa during the austral winter have also declined, but not to the same extent and for the past decade more have been counted during the austral winter than during northward migration. Among those seen at Punta Rasa during the Arctic breeding season have been some with large amounts of rufous breeding plumage. The percentage of such birds has increased from 10–15% in 1987 to 19–54% during 2011–2014. Moreover, observations of individually marked birds show that some of those showing breeding plumage are mature adults, at least 3–7 years old. Conservation actions are required to manage Punta Rasa for the small but important numbers of Red Knots that occur there. Further research is needed to determine why some mature adults do not go to their Arctic breeding grounds and thereby fail to contribute to reproduction. Fil: Martínez Curci, Natalia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Bremer, Esteban. Fundación Vida Silvestre Argentina; Argentina Fil: Azpiroz, Adrián B. Instituto de Investigaciones Biológicas "Clemente Estable"; Uruguay ...